MOLECULAR-GENETIC APPROACH TO PREDICTING THE CLINICAL COURSE OF CHRONIC MYELOPROLIFERATIVE NEOPLASMS (CMPNS) - Jakhonov Azizbek Kholmirzaevich; Matkarimova Dilfuza Saburovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Chronic myeloproliferative neoplasms (CMPNs) are clonal hematopoietic disorders characterized by excessive proliferation of myeloid cells. Clinical outcomes vary widely, ranging from indolent disease to progression into myelofibrosis or acute leukemia. Traditional prognostic models based on clinical parameters often lack precision. Molecular-genetic profiling, including driver mutations (JAK2, CALR, MPL) and additional high-risk mutations (ASXL1, SRSF2, EZH2, IDH1/2, TP53), has significantly improved risk stratification. This study evaluates the prognostic value of molecular-genetic profiling in 150 CMPN patients. An integrated prognostic model combining clinical and genetic factors demonstrated superior predictive power for overall survival (OS) and progression-free survival (PFS). The findings support the use of molecular-genetic approaches for personalized patient management and therapeutic decision-making.